An Investigation of Predictive Marital Adjustment Base of Attachment Styles in Married Women - Seyede Fateme Hoseini Hoseinabad; Bagher Ghobari Banab; Maryam Mashayekh; Sheyda Sodagar; Noorali Farrokhi (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Current figures indicate that many of first marriages in the Iran will end in separation or divorce   and  due to many problems, one of the causing this phenomenon is marital adjustment. Marital adjustment denotes emotional stability, intellectual efficiency and social effectiveness people  and acts as a fundamental contributor to the health and development of family members. One of the most important factors influencing marital adjustment is attachment styles. This study aimed to determine the relationship between attachment styles  and marital adjustment  in women. Methods: This cross-sectional study was conducted on 220 women referring to health centers of yazd city in 2016. The participants were selected via available sampling. The data collection instruments consisted of the standardized Questionnaires include Spanier ’s marital adjustment  (1976) and Collins and Read’s Adult Attachment Style Scale. The data were analyzed in SPSS software (version 19) using descriptive statistics and Pearson correlation coefficient, and stepwise regression analysis, regression equation.  Results: The attachment styles were predictors of marital adjustment. There was a significant negative correlation between marital adjustment  and anxious  and avoidant attachment styles while the correlation between marital adjustment  and securate attachment style was significantly positive. Conclusion: The results showed that the early relationship within the family environment supports a certain attachment style and the effects of the avoidant insecure and ambivalent insecure styles affect the interpersonal relations of the couples in adulthood. As attachment styles are contributory to marital adjustment, counselors can build on couple therapy approach to have an effective role in modifying attachment styles of the couple and solving their conflicts both before and after marriage.